Ambient photolysis frequency of NO2 determined using chemical actinometer and spectroradiometer at an urban site in Beijing - Zou, Q.; Lu, K. D.; Y.S. Wu; Yang, Y. D.; Du, Z. F.; Hu, M. (Frontiers of Environmental Science & EngineeringFrontiers of Environmental Science & Engineering, 2016)
The photolysis frequency of NO2, j(NO2), is an important analytical parameter in the study of tropospheric chemistry. A chemical actinometer (CA) was built to measure the ambient j(NO2) based on a high precision NOx instrument with 1 min time resolution. Parallel measurements of the ambient j(NO2) by using the CA and a commercial spectroradiometer (SR) were conducted at a typical urban site (Peking University Urban Environmental Monitoring Station) in Beijing. In general, good agreement was achieved between the CA and SR data with a high linear correlation coefficient (R-2 = 0.977) and a regression slope of 1.12. The regression offset was negligible compared to the measured signal level. The j(NO2) data were calculated using the tropospheric ultraviolet visible radiation (TUV) model, which was constrained to observe aerosol optical properties. The calculated j(NO2) was intermediate between the results obtained with CA and SR, demonstrating the consistency of all the parameters observed at this site. The good agreement between the CA and SR data, and the consistency with the TUV model results, demonstrate the good performance of the installed SR instrument. Since a drift of the SR sensitivity is expected by the manufacturer, we propose a regular check of the data acquired via SR against those obtained by CA for long-term delivery of a high quality series of j(NO2) data. Establishing such a time series will be invaluable for analyzing the long-term atmospheric oxidation capacity trends as well as O-3 pollution for urban Beijing. (C) Higher Education Press and Springer-Verlag Berlin Heidelberg 2016
Keywords: actinic flux spectroradiometry; atmosphere; chemical actinometer; chinese cities; hong-kong; nitrogen-dioxide photolysis; observatory photochemistry experiment; ozone; pearl river delta; photolysis frequency of nitrogen dioxide; radiometer measurements; rate coefficient; spectroradiometer; tropospheric ultraviolet visible radiation model